IMPLEMENTASI AL ISLAM KEMUHAMMADIYAHAN DALAM MEMBANGUN NILAI RELIGIUS DI PIMPINAN RANTING MUHAMMADIYAH YANGGONG - Sunarno; Nuraini; Muh. Tajab (LPPM STAI Muhammadiyah Probolinggo, 2023)
This research analyzes the implementation of Al-Islam Kemuhammadiyahan (AIK) and its impact on religious values at the Pimpinan Ranting Muhammadiyah (PRM) Yanggong, Jenangan, Ponorogo. The primary focus is identifying the forms of AIK implementation, evaluating its success in shaping the community's religiosity, and identifying the supporting and inhibiting factors of the process. This study is highly significant due to the limited in-depth research on the effectiveness of AIK at the branch level, especially in facing contemporary challenges such as shifts in community mindset and the strong influence of external culture. To achieve these objectives, the research employs a qualitative approach using a case study method at PRM Yanggong. Data collection involved in-depth interviews with key informants (the PRM Chairman, board members, and community leaders), participatory observation of religious and social activities, and the documentation of historical data. All collected data were then analyzed descriptively to gain a comprehensive understanding of AIK implementation. The research findings indicate that AIK implementation at PRM Yanggong is realized through a holistic approach, encompassing formal and non-formal education, dakwah (Islamic propagation), and communal religious practices. This approach has been significantly successful in building religious values, evidenced by enthusiastic participation in worship and the successful purification of aqidah (creed) from takhayul, bid'ah, and khurafat (TBC - superstition, innovation, and myth) in traditions like weddings and funerals. The main supporting factors are strong leadership and active community participation, though shifts in mindset and the penetration of external culture emerged as primary inhibitors.